Plant Parasitic Nematodes in Subtropical and Tropical Agriculture 2018
DOI: 10.1079/9781786391247.0062
|View full text |Cite
|
Sign up to set email alerts
|

Nematode ecology and soil health.

Abstract: This chapter describes the abiotic and biotic components of soil ecosystem structure, and the soil environment as a habitat for organisms. It also discusses the role of nematodes as bioindicators (trophic levels and functional guilds) and as indicators of soil health in agroecosystems. It also presents the guidelines for nematode community analyses. Factors influensing ecosystem services provided by the soil food web are mentioned, which include soil tillage and crop residue management, rotation systems and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 0 publications
2
13
0
1
Order By: Relevance
“…This implies that incorporation of labile organic matter particularly in Irabari, Kaninwathiga and Mutugu will be crucial so as to improve bacterial mediated decomposition (Ferris and Matute, 2003). The two decomposition pathways should be active and coupled in a healthy agricultural system (S anchez-Moreno and Ferris, 2018). The EI values in our study were similar among the eight regions as previously reported (Okada and Figure 3.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This implies that incorporation of labile organic matter particularly in Irabari, Kaninwathiga and Mutugu will be crucial so as to improve bacterial mediated decomposition (Ferris and Matute, 2003). The two decomposition pathways should be active and coupled in a healthy agricultural system (S anchez-Moreno and Ferris, 2018). The EI values in our study were similar among the eight regions as previously reported (Okada and Figure 3.…”
Section: Discussionsupporting
confidence: 86%
“…The CI and EI provide a useful tool for evaluating levels of soil fertility and nutrient resource availability (Ferris et al, 2001). The CI values <50% and >50% denote bacterial and fungal mediated decomposition pathways, respectively (Ferris et al, 2009;S anchez-Moreno and Ferris, 2018). In the present study, the CI values ranged from 39.99 AE 4.90 to 73.58 AE 17.41 indicating the occurrence of both bacterial and fungal decomposition channels across the eight regions.…”
Section: Discussionmentioning
confidence: 61%
“…In recent decades, one significant achievement is the development of a biodiversity perspective to assess soil health, which helps address long‐term sustainability challenges beyond a focus on only crop productivity (Lehmann et al, 2020). Nematodes are the most abundant and functionally diverse Metazoan and have been widely accepted as valuable indicators of soil health (Ferris & Bongers, 2009; Neher, 2001; Sánchez‐Moreno & Ferris, 2018). Indeed, nematodes are distributed in multiple trophic levels within the soil food web and link tightly with plants, microbes, and other soil organisms (Ritz & Trudgill, 1999; van den Hoogen et al, 2019; Yeates et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…After 11 days, which is the period it takes for L. bethae egg to hatch, 5 g of tomato S. lycopersicum (variety: Money Maker) root galls were buried into each L. camara plant of all four aforementioned treatments. This was equivalent to 150 M. javanica females per plant, according to the formula of 1000 μg root galls containing 30 Meloidogyne females . After 62 days, when M. javanica was presumed to have completed a life cycle in the L. camara roots and had formed galls and egg masses, all the L. camara plants in all the treatments were uprooted, washed and inspected for the presence of M. javanica .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Roots and shoots were put into individual brown paper bags, oven dried at 60 °C for 96 h, and weighed. An ANOVA was used to compare dry biomass of plant shoots and roots of various treatments …”
Section: Experimental Methodsmentioning
confidence: 99%